A Portrayal of Changing Oral Condition in Today’s World: A Review - Kajal Kiran Sahoo1 , Sudipta Sahu2 , Debashruti Naik3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
We cannot solve our problems with the same thinking We used when we created them-as stated by Sir AlbertEinstien. Today’s diverse change in the oral condition of the patient needs meticulous understanding by thedentist of the underlying problem and how to solve it in stipulated time, money, environmental and socialcondition of the patient. Health care systems worldwide deliver services for diseased and drug addicts butmost lack oral health care services. Lack of appropriate settings, valid assessment protocol for conductingoral health studies, and poor collaboration between dental and general health care sectors for the diseasedand drug addicts is interfering terribly with the accurate picture of today’s situation. Moreover, lack ofappropriate policies to improve access to dental services, lack of interest among dental professionals intreating the diseased and addicted persons, and low demand for dental care from these sections is leading totoday’s ineffective all-around dental treatment.